2015
DOI: 10.1190/tle34060672.1
|View full text |Cite
|
Sign up to set email alerts
|

A guideline for assessing seismic risk induced by gas extraction in the Netherlands

Abstract: In the Netherlands, seismicity is induced by the reactivation of faults because of the extraction of gas. The Dutch mining law requires a seismic-risk assessment as part of the license application process. For this purpose, a risk-assessment guideline has been developed over the past decade. The guideline contains three assessment levels. At the first level, a screening occurs to assess the potential of inducing seismicity. On the basis of three key parameters and an analysis of the maximum potential magnitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…This is in accordance with the guideline's first step analysis (Muntendam-Bos et al, 2015). The justification is the fact that if the central event (strong ground motion) does not occur, the risk will not occur either.…”
Section: Methodsmentioning
confidence: 48%
See 4 more Smart Citations
“…This is in accordance with the guideline's first step analysis (Muntendam-Bos et al, 2015). The justification is the fact that if the central event (strong ground motion) does not occur, the risk will not occur either.…”
Section: Methodsmentioning
confidence: 48%
“…The guideline presented by Muntendam-Bos et al (2015) identified the need to include the public sensitivity and tolerance to seismicity, and the construction standards of the buildings in the exposed area. As an escalation factor an estimate of the possible extent of damage to infrastructure and buildings and an estimate of the social, financial, and reputational impact of a seismic event was suggested.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations